2022
DOI: 10.3389/fphys.2022.862729
|View full text |Cite
|
Sign up to set email alerts
|

Cooling to Hypothermic Circulatory Arrest by Immersion vs. Cardiopulmonary Bypass (CPB): Worse Outcome After Rewarming in Immersion Cooled Pigs

Abstract: IntroductionCooling by cardiopulmonary bypass (CPB) to deep hypothermic cardiac arrest (HCA) for cardiac surgical interventions, followed by CPB-rewarming is performed on a routine basis with relatively low mortality. In contrast, victims of deep accidental hypothermia rewarmed with CPB generally have a much worse prognosis. Thus, we have developed an intact pig model to compare effects on perfusion pressures and global oxygen delivery (DO2) during immersion cooling versus cooling by CPB. Further, we compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…Extravasation of plasma fluid takes place during normothermic CPB as well as during cooling with intact circulation ( Tveita et al, 1996b ; Hammersborg et al, 2005 ), but increases significantly during hypothermic CPB ( Heltne et al, 2001 ; Farstad et al, 2003 ; Farstad et al, 2005 ; Hammersborg et al, 2005 ). In a recent animal experiment ( Filseth et al, 2022 ), we reported that significantly more fluid volume was needed to achieve adequate perfusion during CPB rewarming from accidental hypothermia over that required in animals after hypothermic cardiac surgery. The results of the present study demonstrated that the need for vascular volume replacement during CPB rewarming was similar between groups, irrespective if terminated during rewarming at 30°C or at 36°C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extravasation of plasma fluid takes place during normothermic CPB as well as during cooling with intact circulation ( Tveita et al, 1996b ; Hammersborg et al, 2005 ), but increases significantly during hypothermic CPB ( Heltne et al, 2001 ; Farstad et al, 2003 ; Farstad et al, 2005 ; Hammersborg et al, 2005 ). In a recent animal experiment ( Filseth et al, 2022 ), we reported that significantly more fluid volume was needed to achieve adequate perfusion during CPB rewarming from accidental hypothermia over that required in animals after hypothermic cardiac surgery. The results of the present study demonstrated that the need for vascular volume replacement during CPB rewarming was similar between groups, irrespective if terminated during rewarming at 30°C or at 36°C.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported the detailed methods for blood flow measurements using this porcine animal model ( Filseth et al, 2022 ). Briefly, a number of 1,000,000, 15 μM diameter fluorescent polystyrene microspheres (Molecular Probes, Eugene, OR, United States) were ultrasonicated, vortex-mixed and injected into the left ventricle (spontaneous circulation) or in the arterial line (cardiopulmonary bypass) four times in different colors (orange [excitation/emission wavelengths: 540/560 nm], yellow-green [505/515 nm], blue-green [430/465 nm], crimson [625/645 nm] and red [580/605 nm]) during the experiment: At baseline, during cooling at 30°C (bladder), during rewarming at 30°C (bladder), and at the end of experiment 2 h after rewarming to 36°C (bladder).…”
Section: Methodsmentioning
confidence: 99%
“…The thermal conductivity of seawater is much higher than that of air. Hence, the core body temperature drops rapidly after a sea fall, leading to acute hypothermia and cold shock response, and causing a series of pathophysiological changes, such as rapidly reducing cerebral blood ow rate, increasing the risk of syncope, and aggravating primary injury [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%